Seismic attributes as the framework for data integration throughout the oilfield life cycle - Marfurt, K. J. (Society of Exploration Geophysicists, 2018)
Useful attributes capture and quantify key components of the seismic amplitude and texture for subsequent integration with well log, microseismic, and production data through either interactive visualization or machine learning. Although both approaches can accelerate and facilitate the interpretation process, they can by no means replace the interpreter. Interpreter "grayware" includes the incorporation and validation of depositional, diagenetic, and tectonic deformation models, the integration of rock physics systematics, and the recognition of unanticipated opportunities and hazards. This book is written to accompany and complement the 2018 SEG Distinguished Instructor Short Course that provides a rapid overview of how 3D seismic attributes provide a framework for data integration over the life of the oil and gas field. Key concepts are illustrated by example, showing modern workflows based on interactive interpretation and display as well as those aided by machine learning.
"2018 Distinguished Instructor Short Course."
Keywords: Seismic prospecting -- Data processing.; Petroleum -- Prospecting -- Data processing.; elektronické knihy; electronic books